(untitled) (Bioscience Journal, 2018)
The study of plant behavior in environments with different luminous intensities offers information about their ability to modify their growth and performance in response to light. The objective of this study was to evaluate the influence of shading on the development of Dimorphandra gardneriana Tul. Different levels of shading were used, with 0% shading (full sun) - (T1), 30% - (T2), 50% - (T3) and 70% shading - (T4). The different levels of shading were obtained by means of black polyolefin screens, sombre type, each treatment consisting of four replicates of 15 plants. The evaluated characteristics were: number of leaves, plant height, neck diameter, survival percentage, shoot length and primary root, green and dry mass of shoots and roots, total dry mass, Dickson quality index and (AP/MSPA), shoot height and diameter (A/DC), aerial part and root dry mass (MSPA/MSR), shoot height and dry mass (CPA/CR), as well as the percentage of roots (%R). The shading influenced negatively the quality of D. gardneriana Â seedlings, being those grown in full sun the ones that presented the best quality. Based on the morphological parameters studied, it can be affirmed that the D. gardneriana Tul., seedlings, produced in an open environment with high luminosity showed superior qualities in relation to the shaded seedlings.